Discovery of 3, 3a, 4, 5-tetrahydro-2H-benzo[g]indazole containing quinoxaline derivatives as novel EGFR/HER-2 dual inhibitors. Issue 32 (10th April 2015) - Zong, Xi; Cai, Jin; Chen, Junqing; Sun, Chunlong; Li, Lushen; Ji, Min
<x xml:space="preserve">Abstract</x> A series of pyrazole–quinoxaline derivatives were synthesized and most of them exhibited potent affinity for EGFR or HER-2 kinase, as well as excellent antiproliferative activity, with compound 4l being the most active.